Pengembangan Data Warehouse untuk Mengetahui Tren Aktivitas Trouble Ticket - Dwi Sartika Simatupang; Sani Muhammad Isa (Universitas Muhammadiyah Riau, 2022)
This research started from the need for XYZ company to be able to present reports or data quickly when needed. There are so many trouble tickets per month, so PT XYZ needs information from historical data that can be seen from various dimensions, especially regarding trends that occur in trouble tickets. With this research, it is possible to develop a data warehouse originating from the operational database from PT XYZ, perform data warehouse analysis with Tableau software to find out trends in trouble ticket activity transactions. The data warehouse development method is to use the nine step design methodology development method using pentaho software. Based on the obtained trends, an information analysis of the number of Trouble tickets was carried out based on two dimensions, namely location and time, and it was found that in the 2nd and 3rd week of each month they had the most trouble tickets. This is due to the influence of the weather in these locations. Then an evaluation was carried out through a questionnaire using the Technology Acceptance Model (TAM), and the average rating from users was 3.83-4.22 which stated that this research could provide benefits and be accepted by PT XYZ.